Romeo and Juliet - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"Romeo and Juliet" by William Shakespeare is a tragedy written between 1591 and 1595. Two young lovers from feuding Italian families meet and fall secretly in love in Verona. Their forbidden romance leads them to marry in secret with a friar's help, hoping to unite their warring households. But family hatred, violent duels, and tragic misunderstandings threaten to destroy their bond. This tale of star-crossed lovers has become the archetypal story of young love and remains one of Shakespeare's most frequently performed plays. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Romeo_and_Juliet
Release date is 1998-11-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: Vendetta -- Drama; Youth -- Drama; Verona (Italy) -- Drama; Juliet (Fictitious character) -- Drama; Romeo (Fictitious character) -- Drama; Conflict of generations -- Drama; Tragedies (Drama)